Bridging Soft Skills and Academic Success: The Mediating Role of Internship Performance - Muhammad Ariq Athallah Akbar; Azizah Akbariani Ahmad; Ayyub Muhajad (Journal of Educational Management Research, 2026)
This study aims to examine the effect of students’ soft skills on academic outcomes, with internship performance serving as a mediating variable. The research addresses the increasing importance of soft skills in higher education, particularly as artificial intelligence reshapes learning environments and demands for both analytical and interpersonal competencies. A quantitative research design was employed, utilizing Partial Least Squares–Structural Equation Modeling (PLS-SEM) to analyze the data. A total of 113 undergraduate students from the Faculty of Economics and Business, Universitas Lambung Mangkurat, who completed internships during 2024–2025, participated in this study by completing structured questionnaires. The results reveal that soft skill dimensions conceptual/analytical ability, teamwork, and information application have a significant positive effect on academic outcomes. Additionally, overall internship performance significantly mediates the relationship between soft skills and academic achievement. These findings suggest that internships not only prepare students for careers but also serve as a critical experiential learning mechanism that enhances academic engagement and performance. The study contributes to educational management by highlighting the role of internship experiences in bridging skill development and academic success, offering practical guidance for curriculum design and experiential learning programs.